THE ROLE OF RENEWABLE ENERGY IN MITIGATING CLIMATE CHANGE - K, Devadasa; N.H, Laxminarayana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper reviews the critical role of renewable energy in addressing climate change, examining how alternative energy sources like solar, wind, hydro, and bioenergy contribute to reducing greenhouse gas emissions. As global carbon emissions reach unprecedented levels, renewable energy technologies have emerged as viable solutions to mitigate environmental impacts while fostering sustainable development. By replacing fossil fuels, renewable energy sources not only reduce carbon emissions but also minimize air pollution, decrease dependency on non-renewable resources, and promote energy security. This study highlights recent advancements in renewable technologies, including cost reductions, improved efficiency, and enhanced scalability, which have accelerated their adoption globally. It also addresses the challenges associated with renewable energy deployment, such as intermittent supply, storage limitations, and high initial costs. Policy interventions, government incentives, and global cooperation are discussed as crucial elements in overcoming these barriers. Furthermore, the paper explores the socio-economic benefits of renewable energy, including job creation and economic diversification, particularly in developing regions vulnerable to climate change impacts. This comprehensive analysis underscores the potential of renewable energy as a transformative force in global climate action and calls for sustained investment, research, and policy alignment to achieve climate goals. The paper concludes by emphasizing the need for continued innovation and collaborative efforts to expand the renewable energy landscape, supporting a transition toward a low-carbon future and resilient ecosystems.